Book Review of Gender Equality and Tourism: Beyond Empowerment edited by Stroma Cole - Li, Wendy; Twining-Ward, Louise (Taylor and Francis, 2019)
Through the tourism sector, poor women around the world have uncovered new revenue-generating opportunities. For many development agencies, that’s a victory. But does increased income automatically lead to increased agency, autonomy, and authority, or in other words, empowerment? Gender Equality and Tourism: Beyond Empowerment provides a timely and accessible examination of the extent to which work in tourism can empower women to transform unequal power relations in favour of women’s rights. Stroma Cole, the book’s editor, argues that economic empowerment is missing the point if it fails to make a lasting change in women’s agency and choices over their own lives. This book is a collection of academic papers originally prepared for a 2016 gender and tourism conference in Turkey.